Perceived parental acceptance-rejection, emotion regulation and socio-behavioural among adolescents in Selangor, Malaysia - Ong, Melissa Ying Sim (2017)
Adolescents are faced with many challenges relating to adjustment to society, and they need support from the public at large in order to thrive as an adult. Indeed, escalating rates of mental health issues and social problems involving adolescents signify the need for all to have a comprehensive understanding of the factors contributing to adolescents’ adjustment in the socio-behavioural domain, in order to improve adolescent functioning and society functioning as a whole. Based on postulates of the Bioecological Model and the Interpersonal Acceptance-Rejection Theory (IPARTheory), an adolescent’s development is heavily influenced by the adolescent’s parents, specifically in terms of their acceptance-rejection behaviours as perceived by the adolescent, where perceived parental acceptance tends to relate to positive child outcome, while perceived parental rejection often leads to negative child outcome. Whereas much research has been done to establish the relationship between perceived parental acceptance-rejection (PAR) and adolescent adjustment, important gaps exist in literature: 1) little is known of the mechanism that links PAR to adolescent adjustment; 2) limited research focused on the socio-behavioural aspect of adjustment; 3) limited similar studies have been conducted in Malaysia. The main aim of this study was hence to fill these gaps and uncover the mechanism that explains how PAR leads to adolescent socio-behavioural adjustment (SBA) by testing the merits of emotion regulation (ER) as a mediator in the relationship. The moderation effects of gender and family income were also examined to understand how the aforementioned relationships differ across subgroups in the population. In addition, differences and similarities between paternal and maternal PAR were examined. The sample consisted of 1,382 students drawn from 33 National Secondary Schools selected around Selangor, Malaysia, using the probability-proportionate-to-size (PPS) sampling method. Adolescent respondents (mean age = 14.5 years) completed self-report questionnaires which contained four measures: Parental Acceptance-Rejection Questionnaire (PARQ) for Father and Mother, Emotion Regulation Index for Children and Adolescents (ERICA), and Personality Assessment Questionnaire (PAQ). Analyses using Structural Equation Modelling (SEM) revealed that as predicted, Malaysian adolescents tended to adjust well socio-behaviourally when they perceived their parents to be accepting, and face socio-behavioural maladjustment when they perceive their parents to be rejecting, regardless of their gender or family income. Most importantly, a significant mediation effect of ER was found using the bootstrap method, indicating that when perceived parental acceptance is high, adolescents tend to be more emotionally regulated which leads them to have better SBA, regardless of their gender or family income. Additionally, examination of latent mean differences across paternal and maternal PAR revealed that adolescents generally perceive their fathers to be colder and more neglecting as compared to mothers. Comparing paternal and maternal PAR in terms of their association with adolescent SBA further showed that adolescents who perceive their mothers to be rejecting become worse off socio-behaviourally than adolescents who perceive their fathers to be rejecting, regardless of their competence in ER. Overall, findings of the present study contributes to our understanding on the pathway through which PAR relates to adolescent SBA via ER, and further provides policy makers and practitioners alike with insights on the factors contributing to adolescent SBA.